IMPLEMENTASI PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR M.HH.02.UM.06.04 TAHUN 2011 TENTANG PEDOMAN PELAYANAN KESEHATAN DI LINGKUNGAN KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DI LEMBAGA PEMASYARAKATAN KELAS IIB PASIR PENGARAIAN - Faradila, Mutia; Firdaus, Emilda; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Health care is a form of realization of the implementation of human rights and is one ofthe elements of welfare that must be realized in accordance with the ideals of the Indonesiannation. All citizens have the right to obtain health services. Article 4 of Law Number 36 of 2009concerning health says